Eight new species and four new records of the leafhopper genus Agnesiella Dworakowska (Hemiptera: Cicadellidae: Typhlocybinae) from China - Wang, Junjie; Liu, Jialing; Zhang, Yalin; Huang, Min (Zootaxa, 2024)
Eight new species of the leafhopper genus Agnesiella Dworakowska are described and illustrated, including Agnesiella (Agnesiella) hamaculeata, A. (A.) nigroflava, A. (Draberiella) biprotrusa, A. (D.) chelata, A. (D.) elongata, A. (D.) galeata, A. (D.) hastata and A. (D.) singuliprotrusa spp. nov. A. (D.) quinquemaculata, A. (D.) kamala, A. (D.) savita and A. (D.) bupa are documented from China for the first time.